1976
DOI: 10.1021/ic50166a022
|View full text |Cite
|
Sign up to set email alerts
|

Structure of [2((CH3)2N)2PCl].AlCl3, ((CH3)2N)3P.((CH3)2N)2PCl.AlCl3, and related species-diphosphorus cations

Abstract: AlCl3, ((CH3),N)3P ‐ ((CH3)2N),PCl‐AlCl3, and Related Species‐Diphosphorus Cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
76
0
9

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 0 publications
2
76
0
9
Order By: Relevance
“…Although complicated, the 31 P NMR solution spectra for the derivatives of 10 exhibit a low-field tripletlike signal that is assigned to a phosphonium center and is distinct from a multiplet that corresponds to the four phosphine centers (Figure 3 a, b). The exclusive formation of 10 a and 10 b from either (PhP) 4 or (PhP) 5 demonstrates a thermodynamic preference for the five-membered framework over the hexaphosphorus or pentaphosphorus alternatives 11 and 12 (Scheme 3) and is consistent with the prominence of the cyclopentaphosphorus unit in Hittorfs phosphorus, [19] polyphosphines, and polyphosphorus anions. [3] Pentaphosphorus cations of type 10 were first proposed on the basis of elemental analysis data for the alkylation products of cyclopentaphosphines.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Although complicated, the 31 P NMR solution spectra for the derivatives of 10 exhibit a low-field tripletlike signal that is assigned to a phosphonium center and is distinct from a multiplet that corresponds to the four phosphine centers (Figure 3 a, b). The exclusive formation of 10 a and 10 b from either (PhP) 4 or (PhP) 5 demonstrates a thermodynamic preference for the five-membered framework over the hexaphosphorus or pentaphosphorus alternatives 11 and 12 (Scheme 3) and is consistent with the prominence of the cyclopentaphosphorus unit in Hittorfs phosphorus, [19] polyphosphines, and polyphosphorus anions. [3] Pentaphosphorus cations of type 10 were first proposed on the basis of elemental analysis data for the alkylation products of cyclopentaphosphines.…”
supporting
confidence: 54%
“…[3] In contrast, comprehensively characterized polyphosphorus cations are limited to phosphinophosphonium 1, [4][5][6][7][8][9] phosphinodiphosphonium 2, [10] diphosphiranodiphosphonium 3, [11] and phosphidodiphosphonium 4 [12,13] ions (Scheme 1). Nevertheless, recent and unique examples of cations 5, [7,14] 6, [15] 7, [8,14,16] and 8 [17] illustrate the potential for diversification and highlight catena-polyphosphorus cations as an underexplored avenue in phosphorus chemistry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the sequence in which the reactants are added determines the products of the reaction: If a I :3 mixture of PC1, and P(NMe2), in CH2C12 is initially prepared, so that the substituent-exchange reaction (1) can occur, then the subsequently added AICI, reacts according to reactions (2) to (4). The reactions are reversible and, as expected from the stoichiometry, reaction (2) becomes predominant with increasing amounts of AICI,; when AlC13 : PCI, is 4 : 1, it is virtually the only reaction.…”
mentioning
confidence: 99%
“…ref. [2]) and subsequently treated with PCI,, then reductive formation of 5 takes place according to reaction (5).…”
mentioning
confidence: 99%